Molluscs (Gastropoda and Bivalvia) of the upper Neretva River - Michael Duda; Elisabeth Haring (Natura Sloveniae)
During a survey taking place from 29.6.2022–2.7.2022 in Bosnia and Herzegovina in the river-floodplain system of the upper Neretva River around Ulog, 51 species of molluscs were found at 12 sampling sites. Besides manual sampling in the water bodies, the main sampling technique consisted of sieving of river deposits, to maximise the coverage of species diversity. The majority of the species were terrestrial gastropods (45 out of 51), most of them common species of forests and moist areas, but also of grassland. In the Neretva River itself and in adjacent waterbodies, six species of freshwater molluscs were found. Among them, at least three species of spring snails of the taxonomically challenging genera Belgrandiella, Bythinella, and Paladilhiopsis were found, the latter one only in river deposits. Future research should focus on truncatelloidean snails in the groundwater system of the upper course of the Neretva River. Furthermore, a broader investigation of the mollusc fauna of Bosnia and Herzegovina would help to clarify taxonomically unresolved questions of species of the Balkan region and possibly reveal species new for science.